2020
DOI: 10.1016/j.rpor.2019.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the predictive value of quantec rectum tolerance dose suggestions on acute rectal toxicity in prostate carcinoma patients treated with IMRT

Abstract: Aim: To investigate the predictive value of convenience of rectum dosimetry with Quantitative Analysis of Normal Tissue Effects in the Clinic (QUANTEC) dose limits, maximum rectum dose (Dmax), total rectal volume (TVrectum), rectal volume included in PTV (VrectumPTV) on Grade 2-3 acute rectal toxicity for utilization in clinical practice. Background: Numerous previous data have reported frequent acute proctitis after external-beam RT of prostate cancer. Predicting toxicity limited with dose information is inad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Any substance can cause toxicity. One of the most important factors to consider in the toxicity of a drug is its dose and how it is exposed 100 . The next important factor is the form of substance, that is, whether it is in form of powder, solution, gas, gel, and so on.…”
Section: Toxicity Definitionsmentioning
confidence: 99%
“…Any substance can cause toxicity. One of the most important factors to consider in the toxicity of a drug is its dose and how it is exposed 100 . The next important factor is the form of substance, that is, whether it is in form of powder, solution, gas, gel, and so on.…”
Section: Toxicity Definitionsmentioning
confidence: 99%
“…The recommended absolute dose-volume parameters for predicting grade 2 acute proctitis were VEQD2-60Gy <9.7cc and VEQD2-50Gy <15.9cc. Also, Ozkan et al(42) showed a significant correlation of RP only with total rectal volume but not with relative dose-volume parameters (V50, V60, V65, V70 and V75) or even the rectal volume included in PTV. Similarly, Kotabe et al(43) suggested that dose-volume constraints referring only to the absolute rectal volume are more reliable.…”
mentioning
confidence: 98%